Patient-specific finite element model of the hip muscles and bones - Jolivet, Erwan; Laredo, Jean-Denis; Bonneau, Dominique; Skalli, Wafa (European Journal of Computational Mechanics, 2009)
Hip fractures are largely considered as a major health-care problem. Several patientspecific finite element models of the isolated femur are proposed to evaluate fracture risk. However, because of their role in femur stress distribution, soft tissue covering the hip should also be considered. Such modeling is particularly complex and major difficulties are related to volumic muscle mesh generation, to specific muscles constitutive equations and numerous contacts within the structure. A method was based on deformation of a parameterized muscle mesh was proposed to get rapidly a patient-specific non distorted mesh. Based in this mesh, finite element model included bones and soft tissues, with surface contact elements between components. Hyperelastic constitutive equations, with hypothesis of incompressibility and isotropy were used to model soft tissue mechanical behavior. Preliminary simulation with quasistatic lateral compression was performed to verify the coherence of the model’s response.